TUMBUHAN PAKU (PTERIDOPHYTA) DI AREA KAMPUS UNIVERSITAS ISLAM NEGERI FATMAWATI SUKARNO BENGKULU - Anggi Prasani; Lisa Puspita; Erik Perdana Putra (Jurnal Biosilampari : Jurnal Biologi, 2021)
This study aimed to determine the types of ferns in the Universitas Islam Negeri Fatmawati Sukarno Bengkulu campus Area which allow them to be preserved and utilized optimally. This research uses descriptive research method. The sampling method uses observation techniques by going directly to the field for observation and sampling. The data obtained from ferns (Pteridophyta) were then identified in the laboratory by observing fern specimens in the form of roots, stems, leaves and spores. Based on the results of research on the diversity of ferns in the UINFAS Bengkulu campus area, 15 species of ferns were found consisting of 13 families, namely Polypodiaceae 2 species, Lygodiaceae 2 species, Davaliaceae 1 species, Dryopteridaceae 1 species, Aspleniaceae 1 species, Lycopodiaceae 1 species, Pteridaceae 1 species, Thelypteridaceae 1 species, Gleicheniaceae 1 species, Selaginellaceae 1 species, Lomoriopsidaceae 1 species, Blechnaceae 1 species, and Psilotaceae 1 species.